AN ANALYSIS OF THE INTERDISCIPLINARITY THEME IN THE MAIN BRAZILIAN JOURNALS ON SCIENCE EDUCATION - Carneiro, Guilherme do Amaral [UNESP]; Cardoso Ferreira, Carlos Roberto; Pansera, Fernanda Cristina [UNESP]; Beduschi, Rian Stenico (Univ Francisco Jose Caldas, Fac Science & Education, 2018)
The discussion on interdisciplinarity has been present in the scope of Education for over 30 years and has had repercussions in the area of Science Education. Despite the many works in the main Brazilian journals in the area, there are still gaps about complementary information on research that relates interdisciplinarity and Science Education. In order to fill some of this gap, we carried out a study whose objective was to identify these approaches in articles of the main national science education journals. We use the terms interdisciplinarity and interdisciplinary as descriptors in the titles, abstracts, and keywords to select the articles analyzed. It was found that studies focus on basic education and deal mainly with curriculum issues. The areas of physics and biology education stand out, as well as the science environment technology society and Environmental Education approaches. Data also point to a contrasting panorama, of diversification and decrease of the research that relates Science Teaching and Interdisciplinarity.
Keywords: science education; scientific journal; analytical bibliography; bibliometrics